2019
DOI: 10.1074/jbc.ra119.007762
|View full text |Cite
|
Sign up to set email alerts
|

Membrane potential is vital for rapid permeabilization of plasma membranes and lipid bilayers by the antimicrobial peptide lactoferricin B

Abstract: Edited by Karen G. Fleming Lactoferricin B (LfcinB) is a cationic antimicrobial peptide, and its capacity to damage the bacterial plasma membrane is suggested to be a main factor in LfcinB's antimicrobial activity. However, the specific processes and mechanisms in LfcinB-induced membrane damage are unclear. In this report, using confocal laser-scanning microscopy, we examined the interaction of LfcinB with single Escherichia coli cells and spheroplasts containing the water-soluble fluorescent probe calcein in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 51 publications
2
48
0
Order By: Relevance
“…local rupture of GUVs at φ m = − 102 mV. In contrast, the rate of membrane permeation of AF647 after local rupture at φ m = − 102 mV is almost the same as that at 0 mV (Hossain et al 2019). These results indicate that the φ m increases the rate constant of LfcinB-caused local rupture but does not change the rate constant of membrane permeation of AF647.…”
Section: Effect Of φ M On Amp-caused Damage Of Guv Membranementioning
confidence: 73%
See 3 more Smart Citations
“…local rupture of GUVs at φ m = − 102 mV. In contrast, the rate of membrane permeation of AF647 after local rupture at φ m = − 102 mV is almost the same as that at 0 mV (Hossain et al 2019). These results indicate that the φ m increases the rate constant of LfcinB-caused local rupture but does not change the rate constant of membrane permeation of AF647.…”
Section: Effect Of φ M On Amp-caused Damage Of Guv Membranementioning
confidence: 73%
“…This rapid membrane permeation is different from the gradual membrane permeation of calcein via magainin 2-caused pores in lipid bilayers (Tamba and Yamazaki 2009). LfcinB also induces membrane permeation of calcein from single E. coli cells stochastically, for example, with 5-μM LfcinB, all examined single cells show membrane permeation of calcein with various rates within 6 min (Hossain et al 2019). However, 5-μM LfcinB cannot induce membrane permeation of fluorescent dye, Alexa Fluor 647 hydrazide (AF647), from most single GUVs comprising E. coli polar lipid extract (E. coli-lipid: phosphatidylethanolamine (PE)/phosphatidyl glycerol (PG)/cardiolipin (CA) [67/ 23/10 (wt% ratio)]).…”
Section: Effect Of φ M On Amp-caused Damage Of Guv Membranementioning
confidence: 84%
See 2 more Smart Citations
“…Antibacterial peptides can be obtained from bacterial cell agglutinating eosinophil cationic protein (RNase 3) and potent analogs were further designed based on the structures [162,163]. An AMP termed lactoferricin derived from the N-terminal of iron binding protein lactoferrin and its shorter analogs were extensively characterized for antimicrobial activity and mechanism [164][165][166][167][168][169][170]. More recent studies have identified several fragments of ApoE protein with broad spectrum antimicrobial activity.…”
Section: Mining the Human Proteome For Novel Ampsmentioning
confidence: 99%